Neonatal cardiac tamponade, a life-threatening complication secondary to peripherally inserted central catheter: a case report - Mohammad Reza Zarkesh; Mokaram Haghjoo (Journal of Medical Case Reports, 2022)
Abstract Background Although the use of a peripherally inserted central catheter (PICC) has many advantages for the treatment of neonates, catheter malposition may result in serious complications that could be life-threatening. We report the case of a 10-day-old neonate with cardiac tamponade secondary to a PICC line who was successfully treated by pericardiocentesis. Case presentation An Iranian (Asian) preterm male neonate was born by Cesarean section with a birth weight of 1190 g and a first-minute Apgar score of 7. Based on an increased respiratory distress syndrome (RDS) score from 4 to 7, resuscitation measures and intubation were performed at the neonatal intensive care unit (NICU). On day 3 after birth, a PICC line was inserted for parenteral therapy. A chest X-ray confirmed that the tip of the PICC line was in the appropriate position. Mechanical ventilation was discontinued 72 h post-NICU admission because of the improved respiratory condition. On the day 10 post-NICU admission, he suddenly developed hypotonia, apnea, hypoxia, hypotension, and bradycardia. Resuscitation and ventilation support were immediately started, and inotropic drugs were also given. Emergency echocardiography showed a severe pericardial effusion with tamponade. The PICC line was removed, and urgent pericardiocentesis was carried out. The respiratory situation gradually improved, the O2 saturation increased to 95%, and vital signs remained stable. Conclusions Dramatic improvement of the neonate's clinical responses after pericardial drainage and PICC removal were suggestive of PICC displacement, pericardial perforation, and cardiac tamponade.